Determinants Of Corporate Value In Construction Sector Companies In 2020-2023 - Widyakto, Adhi; Susanto, Susanto; Rinawati, Tri; Yusof, Rosylin Mohd; Utari, Diah (JURNAL STUDI MANAJEMEN ORGANISASI, 2025)
A construction company is a company that operates in the field of infrastructure development, physical facilities and infrastructure for the benefit of the general public.This study aims to determine and provide empirical evidence related to the determinants of factors that affect firm value in construction companies listed on the Indonesia Stock Exchange in 2020-2023. The type of data used in this study is secondary data in the form of quantitative documentary data.The results of this study indicate that: Liquidity has a significant positive effect on financial distress. Leverage has a significant positive effect on financial distress. Liquidity Profitability has a significant positive effect on financial distress. Liquidity has a significant negative effect on firm value. Leverage has a significant positive effect on firm value. Profitability has a significant positive effect on firm value. Financial distress has an insignificant positive effect on firm value. Financial distress can mediate liquidity on firm value. Financial distress can mediate leverage on firm value. Financial distress can mediate profitability on firm value.